2023
DOI: 10.3390/cancers15041027
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of Membrane Signaling Mechanisms Reduces the Invasiveness of U87-MG and U251-MG Glioblastoma Cells In Vitro

Abstract: Impairing the motility of glioblastoma multiforme (GBM) cells is a compelling goal for new approaches to manage this highly invasive and rapidly lethal human brain cancer. Work here characterized an array of pharmacological inhibitors of membrane ion and water channels, alone and in combination, as tools for restraining glioblastoma spread in human GBM cell lines U87-MG and U251-MG. Aquaporins, AMPA glutamate receptors, and ion channel classes (shown to be upregulated in human GBM at the transcript level and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…GBM43/CTHkd cells expanded over 5 days in culture at varying seeding densities to the same degree as control GBM43 cells ( P = 0.1–0.9; Supplemental Figure 4D ). Similarly, to confirm that the antiinvasive effects of CSE-γ-IN did not reflect effects on cell survival, we assessed the concentration window for which CSE- γ-IN inhibited GBM spheroid invasion without cytotoxicity and found that the invasion inhibitory effect of CSE-γ-IN on spheroids derived from GBM43 cells, which are of the proneural GBM subtype ( 37 ), began at 40 μM ( P < 0.0001; Figure 5D ) with 40 μM CSE-γ-IN also inhibiting spheroid invasion in classical subtype U251 cells ( 38 ) ( P < 0.001; Supplemental Figure 4E ). Concentrations of CSE-γ-IN above 100 μM began to affect the viability of GBM43 or U251 cells ( Supplemental Figure 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…GBM43/CTHkd cells expanded over 5 days in culture at varying seeding densities to the same degree as control GBM43 cells ( P = 0.1–0.9; Supplemental Figure 4D ). Similarly, to confirm that the antiinvasive effects of CSE-γ-IN did not reflect effects on cell survival, we assessed the concentration window for which CSE- γ-IN inhibited GBM spheroid invasion without cytotoxicity and found that the invasion inhibitory effect of CSE-γ-IN on spheroids derived from GBM43 cells, which are of the proneural GBM subtype ( 37 ), began at 40 μM ( P < 0.0001; Figure 5D ) with 40 μM CSE-γ-IN also inhibiting spheroid invasion in classical subtype U251 cells ( 38 ) ( P < 0.001; Supplemental Figure 4E ). Concentrations of CSE-γ-IN above 100 μM began to affect the viability of GBM43 or U251 cells ( Supplemental Figure 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…None of the new ether derivatives displayed significantly improved activity in the current study, suggesting that further chemical modifications at the phenol moiety of 1 are not warranted for antiplasmodial investigations. All new chemistry produced during this project will be added to the Davis Open Access Natural Product-Based Library , and screened in other bioassays in the future.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes from these proof-of-concept late-stage functionalisation studies suggest that with respect to antimalaria potential, further halogenation efforts at C-2 and C-7 are not warranted for this particular scaffold. All new chemistry produced during this project will be added to the Davis Open Access Natural Product-based Library [ 31 , 32 ] and screened in other bioassays in the future. Thus, while compounds 3 – 11 will not directly impact antimalarial drug discovery and development, they may provide future leads for other biomedical applications or be the source of new probes for chemical biology research.…”
Section: Discussionmentioning
confidence: 99%